Low stone wall with trellis - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a low stone wall. Atop the front of the wall stands an empty trellis. A sign behind the trellis reads:" La[nd]scaping [don]e by Garden Cit[y] [L]andscape Co. Garden [mai]ntenance. Specializing [] work, Spanish [] gardens. [Lin]coln Gates, 1268 [Lin]coln Ave." A house is visible in the background on the left of the photograph.